Fuel ethanol production from Eucalyptus globulus wood by autocatalized organosolv pretreatment ethanol–water and SSF. Issue 1 (7th August 2012) - Yáñez‐S, Mauricio; Rojas, Jonathan; Castro, Jean; Ragauskas, Arthur; Baeza, Jaime; Freer, Juanita
Abstract BACKGROUND Lignocellulosic biomass (LCB) offers the only sustainable alternative to the use of fossil fuels as oil by employing its main components (cellulose, hemicellulose and lignin) as a carbon source for the production of biofuels, energy and value‐added chemicals. The aim of the present study was to investigate ethanol production from organosolv pretreated Eucalyptus globulus wood, carrying out the simultaneous sacharification and fermentation (SSF) process at a substrate loading of 10 and 15% (w/v) and using concentrations of 6 and 12 g L−1 of the thermally acclimatized S. cerevisiae IR2T9‐a strain. These SSF experiments were also evaluated by increasing the enzyme loading in the reaction medium. Finally, a comparison was made between separate hydrolysis and fermentation (SHF) and SSF processes. With the information obtained and from published information, a general mass balance was developed. RESULTS The highest ethanol concentration (∼42 g L−1) in the fermentation broth was obtained at a substrate consistency of 15% (w/v), enzyme loading of 20 FPU cellulase 40 UI β‐glucosidase g−1 of pretreated material and using both S. cerevisiae strain IR2‐9a concentrations (6 and 12 g L−1). CONCLUSION The results of enzymatic hydrolysis (EH) show that increasing substrate content from 10 to 15% (w/v) decreases the conversion efficiency of cellulose to glucose. Furthermore, the mass balances of the process indicate that the SSF process is a better alternative than the SHF configuration, because larger amounts of ethanol can be obtained. Copyright © 2012 Society of Chemical Industry